Tensile Strength and Microstructure Analysis of HDPE and PP Plastic Waste-Based Composites with Cassava Pulp Filler: Analisis Kekuatan Tarik dan Mikrostruktur Komposit Berbasis Limbah Plastik HDPE dan PP dengan Filler Ampas Singkong - Wawan Trisnadi Putra; Nanang Suffiadi Akhmad; Munaji; Kuntang Winangun; Arie Mastiko Aji (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2025)
Waste is unused material from human or industrial activities. High Density Polyethylene (HDPE) is a safe plastic, while Polypropylene (PP) is a recyclable thermoplastic, potential as a matrix in composite particle boards. Specimen testing includes tensile tests and macro-microstructural analysis. The highest tensile strength, 23.642 MPa, was found in 100% HDPE composition. A blend of 60% HDPE, 30% PP, and 10% cassava pulp reached 16.026 MPa. In contrast, the lowest strength, 4.420 MPa, was in 60% PP, 35% HDPE, and 5% cassava pulp. Increasing HDPE boosts material strength due to its strong and flexible mechanical properties, but too much cassava pulp weakens it. Macro analysis showed air cavities in the specimen's center, while micro analysis revealed HDPE and PP did not mix homogeneously, with cassava pulp more mixed in PP.